ANALYSING THE FACTORS OF AFFECTING PARENTS’ RESILIENCE IN FAMILIES OF A CHILD WITH AUTISM - Velkoska, Cvetanka; Baki, Esra (International Scientific Journal Vision, 2024)
Having a child in the family, which has an important place in society, is an important life event that affects the entire family system and for many families, it can be a source of stress as well as a source of happiness. Parental stress is related to the type of disability present in the child. Autism is a neurodevelopmental disorder characterized by genetic and environmental factors, usually occurring in the early stages of life causing difficulties in social communication and interaction and the presence of restricted and repetitive behaviors. The fact that their children have autism causes families to experience difficulties in economical, psychological, emotional and social terms, the concept of resilience comes to the fore which makes it easier for families to overcome these difficulties. Social support systems and coping strategies that enable families with autistic children to cope with the difficult situations they experience and coping strategies that enable them to resist stressful events and situations increase the resilience of families, while also enabling them to look at their lives in a more positive way. The aim of this study is to conduct a comprehensive literature review on family resilience levels related to the problems experienced by families with autistic children and to what extent coping strategies, social support systems and perceived stress affect these resilience levels.